Eficacitatea fertilizantului foliar –Reacom Plus [Articol] - Grițcan, Sava; Dadu, Zinaida; Polihovici, Lidia; Crivaia, Parascovia; Nagacevschi, Tatiana (CE UASM, 2013)
The article contains the results of a 2 year study of biochemical composition of apple fruits grown with the use of water-soluble fertilizers as well as of integrated products. It was established that weather conditions influenced the content of monosahara, sucrose separately and less their amount together. The content of dry substances and vitamin "C" remains unchanged. Application of fertilizers on tree development phases has a positive influence on biochemical composition of fruits. It was researched the comparative efficiency of foliar treatment of apple trees with the water-soluble complex fertilizer (Reacom Plus, Fosmex) as well as fertilizers containing nitrogen applied by installments on the background of fertilizers with phosphorus and potassium. It was established that the physiological state of the apple trees improved, the apple harvest increased and duration of fruits storage enhanced.
Keywords: acidity; foliar; complex fertilizers; harvest; monosahara; nutrition; fertilizers; apple tree; water-soluble; biochimical composition; sugar; vitamin “C”